Multiple Process Parameter Optimization of Roll Forming on High Strength Steel using TOPSIS - P, Gopalakrishnaiah.; rao.Ch, Srinivasa; francy .K, Anupama (International Journal of Engineering and Technology, 2018)
The process parameters in roll forming play a significant role in the quality of the end shaped product. The present research deals with an effective approach; TOPSIS has been applied to experimental results of roll forming on high strength steel. The present research focuses on input process parameters including the roll forming line velocity, the inter distance between roll stations, the roll gap, and the diameter of the rolls. The responses considered as a longitudinal strain.Â An optimization procedure TOPSIS (Technique of Order Preference by Similarity to Ideal Solution) originates from the concept of displaced ideal solution. TOPSIS used to predict the optimum process parameter. The main objective of this study is to obtain for minimum elastic longitudinal strains, for each roll station. The results reveals that the inter distance between the roll stations plays a significant role in the roll forming process.Â